Therapies for Membranous Nephropathy: A Tale From the Old and New Millennia - Scolari, Francesco; Alberici, Federico; Mescia, Federica; Delbarba, Elisa; Trujillo, Hernando; Praga, Manuel; Ponticelli, Claudio (Frontiers in Immunology, 2022)
Primary Membranous Nephropathy (PMN) is the most frequent cause of nephrotic syndrome in adults. If untreated, PMN can lead to end-stage renal disease; moreover, affected patients are at increased risk of complications typical of nephrotic syndrome such as fluid overload, deep vein thrombosis and infection. The association of PMN with HLA-DQA1 and the identification in around 70% of cases of circulating autoantibodies, mainly directed towards the phospholipase A2 receptor, supports the autoimmune nature of the disease. In patients not achieving spontaneous remission or in the ones with deteriorating kidney function and severe nephrotic syndrome, immunosuppression is required to increase the chances of achieving remission. The aim of this review is to discuss the evidence base for the different immunosuppressive regimens used for PMN in studies published so far; the manuscript also includes a section where the authors propose, based upon current evidence, their recommendations regarding immunosuppression in the disease, while highlighting the still significant knowledge gaps and uncertainties.